FUSION FACILITY AND GUESTS’ PATRONAGE OF LUXURY HOTELS IN THE NIGER DELTA, NIGERIA - Eugene Onwuli Nwauzi; Joseph Sunday Etuk (Journals Park Publishing, 2025)
The aim of this research, therefore, was to evaluate the effect of fusion facility activities on guests’ patronage of luxury hotels in Rivers State, Nigeria. Descriptive survey research design was adopted for the study; the population of which comprised 246 guests drawn from 10 luxury hotels during the 2023 Christmas festive season in Port Harcourt. Primary data were collected from a well-structured questionnaire, administered on the guests and complimented by secondary data from academic journal papers. Statistical tools for data analyses include; simple percentage, mean scores and standard deviation as well as Multiple Regression Analysis. The findings of the descriptive analysis revealed effective fusion facility service delivery and high guests’ patronage during the period of our investigation. Multiple regression analysis showed that all the 4 indicators of fusion facility attributes (poolside entertainment, rental services, auxiliary services and conferencing) positively and significantly in varied degree, influenced guests’ patronage of luxury hotels in Port Harcourt, Rivers State. Based on the finding, it was concluded that fusion facility dimensions had significant effect on guests’ patronage of luxury hotels in Port Harcourt. In the light of the findings and conclusions of the study, it was recommended that the current service standard should be maintained or improved upon in line with the changing customer preferences and that new guests should be informed of all the services available in the fusion facility.
Keywords: Poolside entertainment. Rental services, Auxiliary services and Conferencing. Patronage.